(untitled) (Revista Educação, Artes e Inclusão, 2025)
This article presents a narrative literature review aimed at analyzing the theoretical paradigms that have influenced educational inclusion practices for people with disabilities. Using the Disability Models as conceptual frameworks for the theoretical foundation of the theme, a historical analysis was carried out covering the period from pre-modern times to the present day. The study highlights the educational implications associated with each model, systematizing their main characteristics and repercussions. In the prescindence model, segregation and marginalization prevailed, with no consistent records of educational practices, except for occasional initiatives of an assistentialist nature. The medical model, in turn, was marked by the logic of integration, in which students with disabilities, once admitted to school, were expected to adapt to existing methodologies, without significant structural or pedagogical transformations. The social model introduced an innovative conception by understanding disability as a result of barriers imposed by society, shifting the focus from individual limitation to social and pedagogical contexts. In conclusion, it is observed that the three models analyzed not only reflect changes in perspective within the educational field but also influence the formulation of legal frameworks and public policies that consolidate inclusion as a structuring principle of contemporary schooling.